Simulated anterior translation and medial rotation of the talus affect ankle joint contact forces during vertical hopping. Issue 9 (3rd July 2020) - Kim, Hoon; Kipp, Kristof
Abstract: The purpose of the present study was to identify the effects of anterior translation and medial rotation of the talus on ankle joint contact forces (AJF) during double-limb vertical hopping. A computational musculoskeletal model was used to calculate AJF under 225 different combinations of 0-10 mm (in 10/15 mm increments) anterior translation and 0-5° (in 5/15° increments) medial rotation for ten subjects. The results show anteroposterior AJF was moderately affected by anterior translation, while mediolateral AJF was strongly affected by medial rotation. Future research should investigate if interventions that manipulate misaligned talus position in-vivo can also reduce AJF.